2018
DOI: 10.1186/s13104-018-3697-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of insecticide treated bed net and associated factors among households of Kola Diba town, North Gondar, Amhara region, Ethiopia

Abstract: ObjectiveThe primary aim of this study was to assess the utilization of an insecticide-treated bed net on the preceding night and associated factors among households of Kola Diba town in 2017.ResultsOf the 260 households, 239 (91.9%) (95% CI = 88.5–95%) utilized insecticide-treated bed net on the night preceding the interview. 242 (93.1%) households didn’t treat the bed net whereas 18 (6.9%) treat the bed net by chemical regularly. Household structure and knowledge about malaria transmission were found to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
0
18
5
Order By: Relevance
“…For example, in this study the amount of change in comprehensive knowledge about malaria was +14.5%. However, even post-intervention knowledge (39.3%) was very low compared to amounts reported in studies in Africa [ 49 51 ] and the national elimination plans, i.e., near 100% for specific item: knowledge of mosquito bite as a correct cause of malaria [ 12 , 13 ]. Studies [ 49 , 50 ] measured specific knowledge items unlike the current study that comprehensively measured knowledge.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, in this study the amount of change in comprehensive knowledge about malaria was +14.5%. However, even post-intervention knowledge (39.3%) was very low compared to amounts reported in studies in Africa [ 49 51 ] and the national elimination plans, i.e., near 100% for specific item: knowledge of mosquito bite as a correct cause of malaria [ 12 , 13 ]. Studies [ 49 , 50 ] measured specific knowledge items unlike the current study that comprehensively measured knowledge.…”
Section: Discussionmentioning
confidence: 95%
“…Spatial variations (study districts), gender, ownershipaccess, exposure to content of school-based messages, perceptions (attitude, perceived efficacy) towards ITN, and a parental perception that students were good reminders were main predictors of ITN utilization. Studies conducted in different regions or settings in Ethiopia reported differences in the prevalence of ITN utilization ranging from 37 to 91% [36,37,51]. Access has been a challenge to ITN usage [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Bed net utilization was signi cantly associated with the presence of either a pregnant mother or under ve years aged children in the household among internally displaced households in the Democratic Republic of Congo (16), household members in the Budondo sub-country in Uganda (28), a national community based survey in Madagascar (30). In agreement with our nding, bed net utilization by SAC was not affected by the presence of pregnant mother or children aged less than ve years in the household in Malawi (45) and general population in Yemen (38).…”
Section: Discussionmentioning
confidence: 99%
“…According to the HBM of health and illness, it is not only the participants' belief that matters but also their knowledge and attitude [47]; hence, the perception of seriousness is based on medical knowledge people own. Better utilisation of ITNs existed among the communities who understand malaria infection and transmission methods [48]. Differences in malaria knowledge have been shown to cause discrepancies in tackling malaria [49] due to differences in strategic utilisation.…”
Section: Insecticide-treated Mosquito Nets and Malaria Knowledgementioning
confidence: 99%